Potensi Pengolahan Produk Kacang Tanah Organik di Desa Cerme, Kapanewon Panjatan, Kabupaten Kulon Progo - Mayasari, Agatha (Jurnal Atma Inovasia, 2023)
Community Service Program is an action taken by students to go directly to the community in implementing the Tri Dharma of Higher Education. The activities carried out are in the form of community service and counseling involving students, lecturers, and the community. This Community Service Program has the aim of increasing knowledge, feeling, and social awareness by providing advice and services at the location of the KKN implementation. With the Real Work Lecture, it is hoped that every student will implement the knowledge they have learned during their studies at the university. The purpose of writing this journal is to explain the village's potential program, namely in developing processed peanut products. This product is later expected to increase income for Cerme Village residents, provide education about the benefits of peanuts, provide additional knowledge about profits, profits, and gross profit in managing product sales. The COVID-19 pandemic is also not an obstacle because digital marketing can work and actually increases the marketing reach for these products.